Crystallization of zinc oxide quantum dots on graphene sheets as an anode material for lithium ion batteries. Issue 2 (12th December 2019) - Tan, Qingke; Kong, Xiangli; Guan, Xianggang; Wang, Chao; Xu, Binghui
Abstract : A zinc oxide quantum dot/reduced graphene oxide (ZnO/RGO) composite is prepared for the first time by a stepped graphene oxide (GO) reduction strategy. Abstract : A zinc oxide quantum dot/reduced graphene oxide (ZnO/RGO) composite is prepared for the first time by a stepped graphene oxide (GO) reduction strategy. Only metal zinc and few-layer GO aqueous suspension are used as starting materials. GO sheets are partially reduced by metal zinc and Zn(OH)2 quantum dots are, in return, generated in the first room temperature Zn reduction step. Zn(OH)2 quantum dots are subsequently transformed into ZnO quantum dots, which catalyze the deoxygenation of the remaining oxygen-containing groups on GO sheets to obtain the final ZnO/RGO product in the second step at 95 °C. As a result, homogeneously distributed ZnO quantum dots with an average particle size of below 10 nm are firmly anchored on the surface of RGO sheets to constitute a micro-sized thin ZnO/RGO composite. The ZnO/RGO composite delivers both high reversible capacities and long cycle life as an anode material for lithium ion batteries.